The model is a reprint of an object in the image - A. A. Kulikov (Российский технологический журнал, 2020)
The problem of facial image recognition (identification) is presented. The difference between facial image recognition and identification is shown. To solve the identification problem, a model of object reprint in the image was developed. This model solves the problem by representing the object in 3-dimensional form, which makes it possible to evaluate and form the necessary characteristics of the object in full, whereas in 2-dimensional form, it is impossible to do this. The model of an object reprint in an image can be used to create a reprint of any spatial objects. To train a reprint model of an object in an image, a multi-layer neural network is used, which is trained sequentially. A local detector for the facial image identification model has been developed to account for acceptable changes in angle, various noise, and different light levels. The binary value that is the result of model processing, represented as activation, determines the relation of a particular image to the corresponding class. The local detector is not only the main element of the model of the object reprint in the image, but it is also a separate mathematical construction. It accepts input data as two-dimensional images. The developed model of object reprint on the image completely solves the problem of identifying a person from the facial image as a whole in conditions of interference and regardless of changes in the angle.